2016
DOI: 10.1007/s10853-016-0515-2
|View full text |Cite
|
Sign up to set email alerts
|

Electric relaxation and Mn3+/Mn4+ charge transfer in Fe-doped Bi12MnO20–BiMn2O5 structural self-composite

Abstract: Fe-doped Bi 12 MnO 20 -BiMn 2 O 5 ceramics was sintered at 1130 K for 6 h in ambient air. Two centro-symmetric phases formed thermodynamically stable self-composite material that was deduced from X-ray pattern analysis. The lattice parameters were a = 10.147 (8) sites. The other relaxation occurred in the 170-220 K range, and it exhibited the following values: s 02 = 10 -11 s, and E A,2 = 0.27 eV. A disorder-related VRH polaron model was proposed for q DC (T) and for electric relaxation processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
(86 reference statements)
1
16
0
Order By: Relevance
“…One phase, BiMn 2 O 5 , consists of octahedrons and pyramids. The second phase, Bi 12 MnO 20 , is dominated by Bi ions and contains BiO 4 tetrahedrons . It is worth mentioning that Bi 12 MnO 20 phase is structurally related to the bismuth oxide, δ‐Bi 2 O 3, structure .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One phase, BiMn 2 O 5 , consists of octahedrons and pyramids. The second phase, Bi 12 MnO 20 , is dominated by Bi ions and contains BiO 4 tetrahedrons . It is worth mentioning that Bi 12 MnO 20 phase is structurally related to the bismuth oxide, δ‐Bi 2 O 3, structure .…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that Bi 12 MnO 20 phase is structurally related to the bismuth oxide, δ‐Bi 2 O 3, structure . Electrical features of ceramic and single crystal forms of the BiMn 2 O 5 compound were studied using broadband dielectric spectroscopy. Two relaxations were discerned in the 100‐450 K temperature range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conductivity in these bulk materials is because of ionic conduction mechanism and governed by the mobility of bismuth (Bi) ions 10 . Effect of calcination on structural properties and consequently on the electrical properties for bulk BiSiO materials have been reported earlier 11,12 .…”
Section: Synthesis Of Bismuth Silicate (Bisio) Nanostructuresmentioning
confidence: 85%
“…The BiMn 2 O 5based component exhibited orthorhombic centrosymmetric Pbam symmetry. The BiMn 2 O 5 structure consisted of Mn 3+ O 5 square pyramids and Mn 4+ O 6 octahedrons [2,[13][14][15]. The XRD measurement showed that in the 0.98 PZT-0.02 BM, a phase transition occurs between two FE rhombohedral phases with point group symmetries of R3c and R3m [3].…”
Section: Introductionmentioning
confidence: 99%